Diagnóstico bacteriológico ambiental de aguas negras del sitio El Guayabo vertidas al río Santa Rosa, y diseño de tanque séptico - Aguilera Torres, Fausto Fabián; Ramón Veintimilla, Perla Samantha (Machala : Universidad Técnica de Machala, 2019)
This research work was focused on the environmental bacteriological diagnosis of sewage water discharged to the Santa Rosa River at the El Guayabo site. For this, a quantitative approach was used, being so cataloged as a descriptive, applied and correlational research, with research techniques such as in situ observation and water analysis. For the water analysis, the presence of biological parameters in water were evaluated, these parameters were Total Coliforms, Fecal Coliforms and Escherichia Coli. Likewise, research instruments that were used during the investigation were a GPS and ArcGis, an informatics program for the creation of maps, both were used to determine the sampling points and their visualization on the respective maps. For the water analyzes, two sampling points were made, the first one before the discharge of sewage water, and the second one, downstream of the alleged discharge. For the analysis of the results obtained from the water analysis, it was proposed to use the Recreational Water Quality Index (RQWI) as an evaluation criteria and the respective environmental bacteriological assessment was carried out. It was obtained that the parameters of Total Coliforms and Escherichia Coli were outside the maximum permissible limits for the use of recreational water established in national regulations such as the Tulsma, and international regulations such as the ones established by EPA, Spain, Peru and Cuba. Therefore, the water quality of the Santa Rosa River is not considered suitable for recreational use downstream of the study sector.
El presente trabajo de investigación se centró en el diagnóstico bacteriológico ambiental de las aguas negras descargadas hacia el Río Santa Rosa en el sitio El Guayabo. Para ello, se utilizó un enfoque cuantitativo, siendo la investigación catalogada como descriptiva, aplicada y correlacional, con técnicas de investigación tales como la observación in situ y los análisis de agua, en los cuales se evaluó la presencia de parámetros biológicos en el agua, como son: Coliformes Totales, Coliformes Fecales y Escherichia Coli. Asimismo, se utilizaron instrumentos de investigación tales como, GPS y ArcGis para la determinación de los puntos de muestreo y su visualización en los mapas respectivos. Para los análisis de agua se realizaron dos puntos de muestreo, el primero antes de la descarga de aguas negras, y el segundo, aguas debajo de la presunta descarga. Para el análisis de los resultados obtenidos de los análisis de agua, se propuso utilizar como criterios de evaluación al Índice para la calidad de agua recreacional y se procedió a realizar la respectiva valoración bacteriológica ambiental. Se obtuvo que los parámetros de Coliformes Totales y Escherichia Coli se encontraban fuera de los límites máximos permisibles para el uso de agua recreacional establecidos en normativas nacionales como el Tulsma, e internacionales como las normativas del EPA, España, Perú y Cuba. Por lo tanto, la calidad del agua del Río Santa Rosa no se considera apta para el uso recreativo que se le da aguas abajo del sector de estudio.
Keywords: AGUA; AMBIENTE; BACTERIOLOGICO; TANQUE SEPTICO